(untitled) (Journal of Health, Technology and Science (JHTS), 2024)
The Food and Drug Monitoring Agency (BPOM) in Gorontalo in 2015 obtained results that 15% of food products were positive for containing dangerous BTP such as borax, formalin, rhodamine B and methanyl yellow. Then in 2017, through the mobile car program, BPOM Gorontalo found four samples that did not meet the consumption requirements out of 412 samples examined. This research aims to determine the prese+ nce of borax content in food sold in the district. Central City, Gorontalo City. The method in this research uses a qualitative approach with the type of research used is descriptive. The type of data used is primary data in the form of research results and secondary data in the form of data search results and various literature and government policies regarding food additives. with a total sample of 15 samples. The results of this research show that of the 15 meatball samples that were examined, 13 samples or 86.7% of meatballs did not contain borax and two samples contained borax or 13.3%.